2014
DOI: 10.1007/s13277-014-2410-2
|View full text |Cite
|
Sign up to set email alerts
|

Impact of neoadjuvant chemotherapy on lymphocytes and co-inhibitory B7-H4 molecule in gastric cancer: low B7-H4 expression associates with favorable prognosis

Abstract: Little is known on the immune response after neoadjuvant chemotherapy (NACT) in gastric cancer (GC). The present study aimed to investigate the effects of NACT on tumor cells and tumor-infiltrating lymphocytes (TILs) in patients with GC. Expressions of CD4+ and CD8+ TILs and identified co-inhibitory B7-H4 molecule were examined by immunohistochemical staining in GC tissues of 56 patients who received NACT (NACT group) and 46 patients who did not receive NACT (nNACT group). These markers, clinicopathological fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 26 publications
0
10
0
2
Order By: Relevance
“…Recent studies have demonstrated various cancer cells and tissues overexpress B7‐H4 protein, and that B7‐H4 protein expression within tumors correlates with various pathological and clinical characteristics. The expression level of B7‐H4 protein in ovarian cancer is related to cancer types, cancer stage, the numbers of Tregs, and patient survival .…”
Section: B7‐h4 Expression and Cancermentioning
confidence: 99%
“…Recent studies have demonstrated various cancer cells and tissues overexpress B7‐H4 protein, and that B7‐H4 protein expression within tumors correlates with various pathological and clinical characteristics. The expression level of B7‐H4 protein in ovarian cancer is related to cancer types, cancer stage, the numbers of Tregs, and patient survival .…”
Section: B7‐h4 Expression and Cancermentioning
confidence: 99%
“…The protein has been found capable of affecting cytokine secretion, T-cell activation, and cytotoxicity abilities [ 5 , 6 ]. B7-H4 has been found in human tumors; in addition to serving as a potential treatment indicator [ 7 , 8 , 9 , 10 ], soluble B7-H4 has been recognized as a possible biomarker for cancer diagnosis [ 11 , 12 ]. Clinical research also revealed that relative to B7-H4+ tumors, B7-H4− tumors are larger (on average) and occur in patients with higher TNM stages [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…In gastric cancer patients, intratumoural infiltrations of cytotoxic T cells and memory cells were shown to indicate better prognoses and survival outcomes [17], while patients with higher tumour-associated microphage (TAM) infiltration had worse surgical outcomes [18,19]. Maskey et al assessed the immune response in gastric cancer patients after neoadjuvant chemotherapy (NACT) and found that those with a low expression of B7-H4 in their tumours had significantly longer OS [20]. Furthermore, the density of mast cell-derived IL-17 had significant positive correlations with microvessels, neutrophils, and regulatory T cells (Tregs).…”
Section: Discussionmentioning
confidence: 99%